Kyoto International Consensus Report on Anatomy, Pathophysiology and Clinical Significance of the Gastroesophageal Junction - A. A. Sheptulin; Y. S. Rabotyagova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Aim: to present the main statements of Kyoto International Consensus report on anatomy, pathophysiology, and clinical significance of the gastroesophageal junction.Key points. The experts reviewed and adopted 28 statements concerning (1) the definition of the gastroesophageal junction (GEJ); (2) the definition of the GEJ zone, covering the area located 1 cm proximal and 1 cm distal in relation to gastroesophageal junction; (3) the assessment of chemical and bacterial (Helicobacter pylori) factors leading to the development of inflammation, metaplasia and neoplasia of the mucosa of the GEJ; and (4) a new definition of Barrett’s esophagus.Conclusion. The new definitions of GEJ, GEJ zone and Barrett’s esophagus adopted by the International Consensus will be used in subsequent studies, which will contribute to improving the results of treatment of diseases of this area.